Readings in Pakistan Foreign Policy, 1971-1998 - Edited by Mehrunnisa Ali (Karachi Oxford University Press, 2001)
This work discusses Pakistan's foreign policy over three decades. Pakistan's relations with the major powers, with its neighbours and the Muslim world are examined. The book also deals with important issues of foreign policy, such as, Kashmir, nuclear issues, and security imperatives.
Include Notes, Tables and Index
Keywords: Pakistan -- Diplomatic relations -- Politics and government